Breaking boundaries : varieties of liminality - Horváth, Ágnes, 1957-; Thomassen, Bjørn (Associate professor); Wydra, Harald (Berghahn Books, 2015)
Liminality has the potential to be a leading paradigm for understanding transformation in a globalizing world. As a fundamental human experience, liminality transmits cultural practices, codes, rituals, and meanings in situations that fall between defined structures and have uncertain outcomes. Based on case studies of some of the most important crises in history, society, and politics, this volume explores the methodological range and applicability of the concept to a variety of concrete social and political problems.